Association Between LENT Score and Survival in Patients with Malignant Pleural Effusion at Dr. Mohammad Hoesin General Hospital, Palembang - Rizkyani Sariza, Fania; Ahmad, Zen; Kurniati, Nova; Yusri, Muhammad; Irfannudin; Sudarto; Andriani, Raden Ayu Linda; Pasaribu, Rouly Pola; Rachman, Alif Fathur (Sriwijaya Journal of Medicine, 2025)
The presence of a malignant pleural effusion (MPE) indicates advanced stage of malignancy, which severely compromises in a poor prognosis. LENT score has been developed as a prognostic tool for MPE, yet its association with survival has not been thoroughly evaluated in Indonesia. This study aims to examine the association between LENT score and 3-month survival in patients with MPE at Dr. Mohammad Hoesin General Hospital, Palembang. This prospective cohort study included 35 patients with MPE. Survival analysis using Kaplan-Meier curves. In this study cohort, the most frequent primary malignancy observed was lung cancer (62,8%). Kaplan-Meier analysis showed a median survival of 22 days for the high-risk LENT scores and 85 days for the moderate-risk group (p < 0,001). LENT score is significantly associated with three-month mortality in EPG patients. LENT score remains a robust tool for risk stratification in MPE management.